PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Harventy, Gina (Jurnal Reviu Akuntansi dan Keuangan)
The purpose of this study is to examine the relation between tax avoidance and the firm value.Tax avoidance is convinced as wealth transfer from the government to companies which hasobligation to enhance firm value. This study uses annual Cash ETR as a proxy for tax avoidanceand Tobin’s Q as a proxy for firm value. The sample of this research is manufacture companieslisted in Indonesia Stock Exchange for the period 2013 to 2015. Using purposive samplingtechnique, we find 35 firms with 105 observations. The statistical methods used in this researchis Linear Regressions Analysis. The empirical results showed that the tax avoidance effect onfirm value.Keywords:Firm Value, Manufacturing Firm, Tax Avoidance